2016
DOI: 10.1186/s12974-016-0570-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the type I interferon response in neurological forms of Gaucher disease

Abstract: BackgroundNeuroinflammation is a key phenomenon in the pathogenesis of many neurodegenerative diseases. Understanding the mechanisms by which brain inflammation is engaged and delineating the key players in the immune response and their contribution to brain pathology is of great importance for the identification of novel therapeutic targets for these devastating diseases. Gaucher disease, the most common lysosomal storage disease, is caused by mutations in the GBA1 gene and is a significant risk factor for Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 69 publications
10
64
0
Order By: Relevance
“…Gene expression profiling microarray analysis was performed as described [9], but using RNA from the VPM/ VPL region of Gba flox/WT ;nestin-Cre mice and Gba flox/flox ; nestin-Cre mice at 10 days of age.…”
Section: Gene Expression Profiling Microarray Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression profiling microarray analysis was performed as described [9], but using RNA from the VPM/ VPL region of Gba flox/WT ;nestin-Cre mice and Gba flox/flox ; nestin-Cre mice at 10 days of age.…”
Section: Gene Expression Profiling Microarray Analysismentioning
confidence: 99%
“…The most consistent neuropathological finding reported in human nGD patients is accumulation of lipid-laden macrophages as well as neuronal loss and neuroinflammation [3]. The use of mouse models of nGD [4][5][6] has resulted in the discovery of additional pathways involved in neuropathology, such as neuronal loss [7], neuroinflammation [8] and activation of specific signaling pathways [9,10]. The Gba flox/flox ; nestin-Cre mice [4], a commonly used nGD mouse model, exhibits rapid motor dysfunction associated with severe neuroinflammation and neuronal loss starting at 14 days of age, and develops paralysis by 21 days.…”
mentioning
confidence: 91%
“…Nevertheless, the precise contribution of neuroinflammation to disease progression is currently unclear (Vitner et al, 2014(Vitner et al, , 2016. proposed to impact pathogenesis (Archer et al, 2014;Arfi et al, 2011;Wilkinson et al, 2012).…”
Section: Gaucher's Disease Mucopolysaccharidosis Niemann-pick Type Cmentioning
confidence: 99%
“…A recent study by Taylor and colleagues has shown increased expression of IFN-I in the brains of patients with Alzheimer's disease (AD; Taylor et al, 2014). Moreover, findings in mouse models for Gaucher disease and Krabbe disease suggest that IFN-I contribute to the neuroinflammation present in some neurodegenerative lysosomal storage diseases (Vitner et al, 2016). This is contrasted by other studies that have yielded conflicting results, indicating a neuroprotective role for IFN-I in the murine and human CNS with AD-like neurodegeneration (Ejlerskov et al, 2015;Grimaldi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%